1997
DOI: 10.1063/1.473866
|View full text |Cite
|
Sign up to set email alerts
|

Interaction potential of Al3+ in water from first principles calculations

Abstract: We present a parametrization of the interaction potential for Al3+ in water from first principles calculations. We have performed a critical study of the Al3+–water interaction using sequences of correlation consistent basis sets that approach the complete basis set limit and include core-valence correlation effects. We suggest as minimum theoretical requirements treatment of the electron correlation at the MP2 level of theory using a triple zeta quality basis set that accounts for the effect of core-valence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
82
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 71 publications
18
82
2
Order By: Relevance
“…Therefore, many-body interactions, including polarization, are included in a parameter free way as the simulation proceeds. For highly charged ions, it has been demonstrated that AIMD works reliably [12][13][14]21 and we will show that there is very good agreement between simulated extended x-ray absorption fine structure ͑EXAFS͒ spectra and the results of measurements.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, many-body interactions, including polarization, are included in a parameter free way as the simulation proceeds. For highly charged ions, it has been demonstrated that AIMD works reliably [12][13][14]21 and we will show that there is very good agreement between simulated extended x-ray absorption fine structure ͑EXAFS͒ spectra and the results of measurements.…”
Section: Introductionmentioning
confidence: 89%
“…9͒ based on empirical potentials or by ab initio molecular dynamics ͑AIMD͒. 10,11 Modeling charged ions in solution is challenging because the water molecules surrounding the ion are strongly polarized; [12][13][14] we have recently reported water dipole moments increasing by Ϸ1 D relative to bulk water values for the first hydration shells of the Al 3+ and Fe 3+ ions. 14 In this article, we report simulation of the properties of the Zn 2+ ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Also, the methodology has recently been extended by proposing a low-cost technique for the generalization of the HIW potential to other small and highly charged cations like Be 2ϩ , Mg 2ϩ , and Al 3ϩ . 42 The validity of this approach has also recently been tested by other groups [43][44][45][46] and was pointed out by Cordeiro et al 47 in an earlier Cu 2ϩ hydration study. In particular, Bleuzen et al 43 have studied the water-exchange mechanism for the second hydration shell of the Cr 3ϩ , assuming in the ionwater interaction potential the existence of the hexahydrate and selecting the nonelectrostatic parameters of the ionsolvent potential in such a way that MD simulations produced the closer results to experimental properties.…”
Section: Introductionmentioning
confidence: 90%
“…[20][21][22][23][24][25] Their results also point out the advantages of this approach to describe a wide set of physicochemical properties of ionic solutions.…”
mentioning
confidence: 99%